Impact of VAPE use on dental and oral health among male dental students - Khalaf, Mohammed Hassan; Alwan, Maryam Hameed (Indonesian Journal of Dental Medicine, 2025)
Background: The emergence of vaping as a popular alternative to traditional smoking has raised concerns regarding its potential impact on oral health. specifically affects the oral health of dental students, who are not only consumers of these products but also future practitioners tasked with educating patients on oral hygiene and health risks. purpose: This study investigated the dental and oral health impact of VAPE among male dental students. Methods: A self-administered questionnaire comprising 20 questions was meticulously designed to gather relevant data about their VAPE use and its implications on dental and oral health. Results: 43% of participants reported using VAPE, predominantly employing salt nicotine (48.8%) over free base nicotine (27.9%). The dental health statuses, assessed using the Decayed, Missing, and Filled Teeth (DMFT) index, showed that 35.6% had a DMFT score of 3 or higher, while 37.6% had scores below 3, and 26.7% reported a DMFT of 0. Most participants (57.4%) visited the dentist rarely, with no distinction between VAPE users and non-users. However, significant differences in aspects such as breathing, sleep quality, and fitness were noted between VAPE users and non-users (p:0.002, p:0.05, and p:0.00; p<0.05), respectively. Conclusion: As E-cigarettes smoking is becoming more widely growing habit within the young age group, more oral and physiological consequences begin to rise, such as a significantly higher prevalence of mouth dryness, cough and ultimately, worsened bodily functions including a lower breathing quality and reduced level of fitness.